Mobile payments systems in Kenya : a new era or a false dawn? : an examination of the legal and regulartory issues arising 'post' financial inclusions - Malala, Joy Nabwire (2014)
This study, for the first time, brings together the detached understanding that facilitates coherent analysis of the emerging legal and regulatory issues that mobile payments introduce after financial inclusion in Kenya. To pursue these arguments firstly the thesis finds that the law on payments systems is incomplete as it does not address the specific issues necessary for an effective payments systems. It also puts forward the argument that the current regulatory regime is weak and largely unfelt due to its nascent state of development. Furthermore the current legal instruments are dispersed, and not uniformly applied among and across all payments systems and instruments as there exists an ambiguity in the legal definition of ‘mobile money’ and ‘deposits’ that present legal challenges in the enforcement of new regulations. Secondly, the cross-roads between the telecommunications industry and the financial industry that introduces non-banks into the retail payments market, presents a challenge in its effective regulation. As policy objectives are blurred when firms which are traditionally separated have to find appropriate regulatory frameworks in convergence. Thirdly this thesis examines the approach taken by Kenya in regulating mobile payments juxtaposing the realities that combine to blunt the impact of innovation and access to finance. This thesis serves as a foundational discussion on the regulatory capacity for the adoption and development of mobile payments within a regulatory vacuum and proposes that an appropriate regulatory framework is needed to addresses all these issues.